Equity, access to and democratization of higher education: Report of current policies in practices in Israel - Forkosh Baruch, Alona; Heart, Tsipi; Arad, Judy; Hardof, Sharon; Govrin, Shevi; Gnizi, Itzik; Manor, Gal (PRATICA - Revista Multimédia de Investigação em Inovação Pedagógica e Práticas de e-Learning, 2022)
The Israeli society is diverse, both ethnically and economically. Its population is composed of 22% non-Jewish minorities including Muslims, Bedouins, Christians and Druze, most living in low socio-economic locations. Among the Jewish majority, there are ultra-orthodox (8%) and Ethiopian-origin (1.5%) groups, as well as populations living in geographic and low socio-economic periphery. Such a diverse society brings challenges in terms of equity, access and democratization of higher education. The present report, performed for the Love.Dist@nce project aims to review and summarize the main practices and policies in Israel on this topic.